Optimized lovastatin production by solid-state fermentation using agro-industrial derived substrates - Cabral, Maria Eugenia (2011)
Lovastatin is a drug that can inhibit the de novo synthesis of cholesterol by competitive inhibition of HMG-CoA reductase, which catalyzes the rate limiting step of cholesterol biosynthesis. It can be then effectively used for the hypercholesterolemia treatment. Nowadays, interest has focused in searching new statins and/or developing low-cost production strategies. This work aimed at optimizing lovastatin production by solid state fermentation (SSF) with Aspergillus terreus MEC, looking for low-cost and readily available substrates. Cultures consisted in textured deffated soy bean flour (HSDT) embedded with A. terreus-inoculated LP (whey protein concentrate) or SQ (whey) liquid media. Different initial pHs (4.3, 5.3, 6.3, 7.3), incubation temperatures (23, 25, 28, 30°C), moisture contents (CHI: 36, 46, 56, 66, 76%) and bed heights (1, 1.5, 2, 2.5, 3, 4 cm) were evaluated. Extracted lovastatin was analyzed by RP-HPLC with a Diode Array Detector and fungal growth was indirectly determined by ergosterol quantification. A lovastatin production of 1017.55 µg per g of dry weight was reached by using optimized SSF consisting in SQ liquid medium adsorbed on HSDT at an incubation temperature of 25°C, pH = 6.3, CHI = 46-56% and a bed height of 1.5-2.5 cm. These results highlight the relevance of SSF strategies for the production of high-added-value secondary metabolites.